PENERAPAN SISTEM PERANGKAT PENILAIAN PADA KAWASAN PERUMAHAN, STUDI KASUS KAWASAN PERUMAHAN DI KOTA BOGOR, INDONESIA - Rejoni, Rahmat; Sulistyantara, Bambang; Fatimah, Indung Sitti (Jurnal Lanskap Indonesia, 2016)
Sustainable regional development is one of the government program, but in Indonesia there has been no direct assessment for the sustainable region. This is caused by the assessment tools that available now is not completed yet. Objectives of the study were to compare some assessment tools to formulate the considered best tools; to analyze the practice of one of the green assessment tools in Indonesia, specifically sustainable regional development assessment tools for a residential area in Bogor City; and to give an overview for the residential area that has green concept development generally in Indonesia and Bogor City in particular. Result of this study shows that the assessment tools in Indonesia still needs improvement, and that the green concept of the researched residential area is not suitable with criteria from assessment tools. Thus recommendation is proposed, based on minimum score of the existing assessment tools.